(untitled) (Docentes 2.0 Journal, 2025)
Educational settings are transforming with technological advances and recent global circumstances, driven by the implementation of virtual and in-person teaching modalities for learning English as a foreign language. This research analyzed students’ perceptions in the Pedagogy of National and Foreign Languages ??program regarding their language learning in both virtual and in-person modalities. It was based on the pragmatic paradigm, comparative historical method, mixed approach, sequential exploratory design, multiple integration, and cross-sectional design. The study population comprised 56 students in the Pedagogy of National and Foreign Languages ??program at the Peninsula State University of Santa Elena, Playas Campus. Structured surveys and semi-structured interviews were combined. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The results revealed a strong preference for the in-person learning modality, highlighted by its ability to foster direct interaction and the use of English language skills. In contrast, the virtual modality is valued for its flexibility, access to digital resources, and support for independent learning. However, students noted significant limitations, such as limited direct interaction with peers and technical issues related to connectivity and devices. This study underscores the importance of implementing pedagogical strategies that leverage the advantages of both modalities and overcome their limitations.